Revisiting African Religion as an Academic Discipline in Africa: History and Prospects - Kivinge, Ivan B (Zamani: A Journal of African Historical Studies, 2024)
Three main religious traditions—indigenous African beliefs and practices (African religion), Christianity and Islam—have dominated everyday life of communities in Africa today. Scholarship on religion indicates that only African religion originated in Africa—Christianity and Islam are foreign religions. Many Africans today have been active Christians and Muslims, who are sometimes being misleadingly taught that African religion is demonic and forms of paganism. This article employs historical and philosophical approaches to show how the study of African religion has navigated through various historical currents and resultant implications on the way the current generation views it. In the end, the article proposes an impartial approach to the study of African religion. It is premised on the argument that African religion is there to stay, both as an academic discipline and a spiritual entity despite the challenges.